Guide to good writing [Viva-facts on file] - Manser, Martin H. (New Delhi : Viva Books Pvt.Ltd., 2007)
Guide to Good Writing is an indispensable guide to the basics of good writing. Everywhere in the modern world the emphasis is on speed, and nowhere have things moved faster than in communications. messages travel at the speed of light, and we humans seem to feel that we have to imitate the wonderful machines that flash our words around the globe in fractions of a second. We have become a race of scribbles, jotting memos, punching in text messages, rushing off-e-mails, and dashing off quick .
Include bibliographical reference, index.
Keywords: Writing-guide